2020
DOI: 10.1186/s10194-020-01177-4
|View full text |Cite
|
Sign up to set email alerts
|

Improvements across a range of patient-reported domains with fremanezumab treatment: results from a patient survey study

Abstract: Background: The long-term safety and efficacy of fremanezumab were evaluated in a 52-week extension study (NCT02638103). Patient satisfaction with fremanezumab, dosing preferences, and patient-reported outcomes were assessed in a subpopulation who completed the extension study and consented to a follow-up questionnaire. Methods: In the extension study (N = 1842), adults with migraine were randomized to quarterly or monthly fremanezumab. After completing active treatment, patients answered a survey evaluating p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 23 publications
1
12
0
1
Order By: Relevance
“…In a long-term extension study following the pivotal 3-month studies of fremanezumab in CM and EM, efficacy was maintained for a further 12 months of treatment, with no evidence of wearing off at the end of the quarterly or monthly dose intervals [18,24]. Additionally, patients reported high levels of treatment satisfaction, as well as improvements in sleep quality, reduced anxiety and increased quality of time spent with others [25]. However, real-world effectiveness, treatment persistence and adherence data are limited for fremanezumab and other CGRP pathway-targeting mAbs for the prevention of CM or EM.…”
Section: Background and Rationalementioning
confidence: 98%
“…In a long-term extension study following the pivotal 3-month studies of fremanezumab in CM and EM, efficacy was maintained for a further 12 months of treatment, with no evidence of wearing off at the end of the quarterly or monthly dose intervals [18,24]. Additionally, patients reported high levels of treatment satisfaction, as well as improvements in sleep quality, reduced anxiety and increased quality of time spent with others [25]. However, real-world effectiveness, treatment persistence and adherence data are limited for fremanezumab and other CGRP pathway-targeting mAbs for the prevention of CM or EM.…”
Section: Background and Rationalementioning
confidence: 98%
“…51 Though no difference was seen in the efficacy of quarterly and monthly doses, results from the HALO study (NCT02638103) showed that 69% patients preferred quarterly fremanezumab. 52,53 In addition to reaching the migraine related efficacy end-points, patients also reported improvement in quality of time spent with others, anxiety and sleep quality. 53 The most commonly reported TEAEs were injection site reactions like induration, pain and erythema.…”
Section: Fremanezumabmentioning
confidence: 99%
“…52,53 In addition to reaching the migraine related efficacy end-points, patients also reported improvement in quality of time spent with others, anxiety and sleep quality. 53 The most commonly reported TEAEs were injection site reactions like induration, pain and erythema. 51,52 EPTINEZUMAB Eptinezumab (VYEPTI TM ) was approved by the US-FDA in February 2020 for the prevention of migraine in adults.…”
Section: Fremanezumabmentioning
confidence: 99%
“…Actualmente se han publicado un metaanálisis (n = 3.404) 41 y un pool data-análisis (n = 2.566) 42 que han concluido que la seguridad y pacientes con fremanezumab presentan mayor número de días sin nada de dolor y estado funcional normal que los pacientes tratados con placebo (n = 563) 53 . Además, se ha observado una mejoría significativa en la calidad del sueño, la ansiedad y la calidad del tiempo pasado con allegados (n = 253) 54 .…”
Section: Seguridad Y Tolerabilidad Del Fremanezumabunclassified